The capture of the mangrove crab (Ucides cordatus) in the estuarine system of Santos-são Vicente: Ethnoecology of the fishermen from vila dos pescadores, Cubatão (SP), Brazil - Machado, Ingrid Cabral; Piccolo, Nátali; Barros, Márcia Rocha; Matsunaga, Akeme Milena Ferreira [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (Boletim do Instituto de Pesca, 2018)
‘Uçá’-crab (Ucides cordatus) is a fishery resource used by artisanal fishermen at ‘Baixada Santista’, São Paulo coast, very important for subsistence of countless families. Since 2014, law restrictions to capture of this species were generated actions to crab catch ordination in this region and in this process, an ethnoecological research was carried out. Among the fishermen’s groups in the region, the ‘Vila dos Pescadores’ at Cubatão (SP), is the most important in relation to the crab catching of ‘uçá’-crab. Between June 2015 and April 2016 were applied structured interviews to crab catchers in this same locality. Results obtained according socioeconomic and productive profile of these catchers, distinct management and rules of use of this resource, the product commercialization and possible actions concerning to better life condition of these crab catchers are discussed in present study. This information will be useful as subside to fishery ordinance, and to recognize the knowledge of these artisanal fishermen that have a dependence of this fishery resource.
A captura do caranguejo-uçá (Ucides Cordatus) no sistema estuarino de santos-são Vicente: A etnoecologia dos catadores de caranguejo da vila dos pescadores, Cubatão (Sp), Brasil
Keywords: Baixada Santista; Crab; Estuary; Ethnoecology; Mangrove